Safeguarding Deaf Children: A Multi-agency Focus on Actions for Change. Issue 3 (27th May 2018) - Wilson, Shirley; Attrill, Michelle; Critchley, Tracey; Clements, Daniel; Hornsby, Joanne; Mullen, Christopher; Miller, David; Redfern, Paul; Richardson, Tim; Stow, Lynn; Young, Alys
Abstract : This article concerns safeguarding deaf children and is written by a dedicated multidisciplinary consortium of national organisations, service providers and academics in the UK. Data are derived from 81 senior managers in social care, health, education, the police and voluntary sector organisations who attended a specialist conference concerning deaf children and safeguarding and who participated in three structured workshops. Thematic content analyses revealed their perspectives on risks and barriers to safeguarding deaf children at practice and organisational levels. An impact/effort matrix structure was used to elicit from participants a series of actions to improve practice and these were thematically organised. Findings are discussed in the context of the 2018 revisions to 'Working Together' in England, statutory reforms to PHSE in schools in England and recent NICE revised guidance on Child Maltreatment. Implications for practice are highlighted.